Improving tomato yield and production economics with Nano-NPK fertilization and salicylic acid chemigation - Zhenhao Guan; Khandakar Rafiq Islam; Arifur Rahman; Brad Bergefurd (PLoS ONE, 2026)
Nanotechnology-enabled NPK fertilization combined with biostimulants offers a sustainable approach to enhance crop productivity, resource-use efficiency, and environmental performance in specialty crops. A two-year (2022−2023) factorial experiment (3 × 2), arranged in a completely randomized design, evaluated the interactive effects of nano humic acid–silicic acid-based Triple 20 NPK fertilizers (nano-NPK) applied at 40, 80, and 120 kg ha ⁻ ¹, with and without 0.3% salicylic acid (SA) as biostimulant, on processing tomato ( Solanum lycopersicum L. cv. BHN 685) grown in a low-fertility soil under drip-irrigated, raised bed plasticulture. Conventional Triple 20 NPK fertilization at 120 kg ha ⁻ ¹ served as the control. Multivariate statistical analyses demonstrated that nano-NPK fertilization and SA, alone or in combination, significantly improved tomato yield components, water use efficiency (WUE), and fertilizer use efficiency (FUE), while reducing cull fruit and increasing marketable yield. Among treatments, 80 kg ha ⁻ ¹ nano-NPK combined with 0.3% SA produced both total and marketable yields equivalent to or exceeding those obtained with 120 kg ha ⁻ ¹ nano-NPK or conventional fertilization, alongside higher nutrient, and water utilization. These improvements were associated with enhanced nutrient bioavailability, uptake, and photosynthetic performance due to nano-enabled NPK fertilization, with SA further promoting plant growth and fruit quality. This combination reduced fertilizer input by up to 33% without compromising yield, achieving WUE and FUE comparable to or better than conventional NPK fertilization (120 kg ha -1 ). Economically, 80 kg ha ⁻ ¹ nano-NPK + 0.3% SA achieved the highest benefit–cost ratio (1.26) and net return (US $1,988 ha ⁻ ¹), outperforming conventional NPK fertilization. Environmental assessment indicated improved energy use efficiency (4–6%) and lower greenhouse gas (GHG) intensity per unit of marketable yield. Although total GHG emissions were statistically similar at higher application rates, nano-NPK, SA, or their combination reduced GHG intensity, highlighting their sustainability advantage. Overall, integrating 80 kg ha ⁻ ¹ nano-NPK with 0.3% SA optimizes yield, profitability, and environmental stewardship, offering an efficient pathway for sustainable intensification of tomato production.